The Devil's Own Duke - Bell, Lenora (New York, NY : Avon Books, an imprint of HarperCollins Publishers, 2021)
Forced to marry gambler Ash Ellis to keep her beloved vineyards, Lady Henrietta Prince finds that all bets are off when his kisses are more intoxicating than the finest of wines even though he will never have her trust.
Keywords: Aristocracy (Social class) -- Fiction; Man-woman relationships -- Fiction; Marriage -- Fiction; Regency fiction; Historical fiction; Romance fiction